Buttressing customer relationship management through digital transformation: perspectives from zimbabwe’s commercial banks - Prosper Raphael Kaondera; Lovemore Chikazhe; Tinotenda Fredrick Munyimi; Brighton Nyagadza (Cogent Social Sciences)
As a way of buttressing customer relationship management, it is prudent that banks integrate digital transformation as a matter of urgency. To this end, our study’s objective was to establish the contribution of digital transformation on customer relationship management within the banking sector. Our study was hinged on Technology Acceptance Theory and the Identify, Differentiate, Interact and Customise Theory. The sample (348) for the study was drawn from 5 commercial banking employees, and these were randomly selected. A structured questionnaire with Likert type questions was used to collect data, which was analysed using SPSS. Our research findings indicate a positive relationship between digital transformation and customer relationship management. The current study recommends measures that guide the development of digital transformation processes within the banking sector. This research is important as it provides solutions, which can assist management and contact centres for commercial banks to manage customer relationships in modern business. Specifically, our research introduces a new e-customer relationship management system that is technically embedded into e-banking channels.